Dulaglutide and incident atrial fibrillation or flutter in patients with type 2 diabetes: A post hoc analysis from the REWIND randomized trial. Issue 4 (24th January 2022) - Raubenheimer, Peter J.; Cushman, William C.; Avezum, Alvaro; Basile, Jan; Conget, Ignacio; Dagenais, Gilles; Hoover, Anastasia; Jansky, Petr; Lanas, Fernando; Leiter, Lawrence A.; Lopez‐Jaramillo, Patricio; Pogosova, Nana; et al.
Abstract: Aim: To assess the occurrence of atrial fibrillation or atrial flutter (atrial arrhythmias [AA]) in patients with type 2 diabetes treated with once‐weekly subcutaneous dulaglutide versus placebo. Materials and Methods: Patients without electrocardiographic (ECG)‐confirmed AA at baseline and randomized in the REWIND trial were assessed for the development of AA based on an annual ECG. Additional analyses included whether dulaglutide compared with placebo reduced the composite outcome of AA or death, AA or cardiovascular death, AA or stroke and AA or heart failure. Results: Among 9543 participants (mean age 66 ± 7 years, with cardiovascular risk factors and 31% with previous cardiovascular disease) without AA at entry in the trial, 524 patients (5.5%) had at least one episode of AA during the median 5.4 years of follow‐up. Incident AA occurred in 269 of the 4769 participants allocated to dulaglutide (5.6%), at a rate of 10.7 per 1000 person‐years, versus 255 of the 4774 allocated to placebo (5.3%), at a rate of 10.5 per 1000 person‐years ( P = .59). There was also no effect of dulaglutide on the composite outcome of AA and death or AA and heart failure. Conclusion: This post hoc analysis of data from the REWIND trial showed that treatment with dulaglutide was not associated with a reduced incidence of AA in this at‐risk group of patients with type 2 diabetes.